Designing an Integrated Model of Vocational Training and Social Assistance in Social Rehabilitation Centers - Widiansyah, Wiwit; Ardiwinata, Jajat Sudrajat; Kamil, Mustofa; Saepudin, Asep; Azzasyofia, Mira (Studies in Learning and Teaching, 2025)
This study addresses the challenges in improving social rehabilitation services for beneficiaries through vocational training and social assistance in social rehabilitation centers. The purpose of this study is to design and propose a model for integrating vocational training and social assistance and to identify factors that support the model's implementation. The research method is quantitative, employing a survey of 41 individuals, which represents 39% of the 105 total population of social workers for social welfare service recipients across several social rehabilitation centers. The research findings reveal that vocational training and social assistance in social rehabilitation centers are currently carried out as separate programs, lacking a unified implementation framework. Although social assistants play a significant role during the mapping and evaluation stages, their involvement in the integration and execution of both services remains limited. These insights underscore the need to design a more cohesive and collaborative model that bridges vocational empowerment with social support mechanisms. The novelty of this study lies in its holistic approach, which emphasizes not only the improvement of job skills but also the strengthening of psychosocial aspects. This model is designed to enhance the effectiveness of social reintegration and independence for beneficiaries, areas that have not been widely addressed in an integrated manner in conventional social rehabilitation programs.